SMART TECHNOLOGIES AS A LEVEL INDICATOR AND QUALITY OF LIFE - Aleksey M. Karmanov (Статистика и экономика)
In the twenty-first century, many economically developed countries of the worldare turning their attention toward smarttechnologies, such as special areas ofvital importance for the current and futuredevelopment of society. In this regard, a great scientiﬁc and practical value judgment, speciﬁcation and content analysisof the place and role of smart technologyas a visual indicator of the level and quality of life.